A phase II trial of bendamustine in combination with rituximab in older patients with previously untreated diffuse large B‐cell lymphoma. (22nd July 2016) - Park, Steven I.; Grover, Natalie S.; Olajide, Oludamilola; Asch, Adam S.; Wall, James G.; Richards, Kristy L.; Sobol, Anna L.; Deal, Allison M.; Ivanova, Anastasia; Foster, Matthew C.; Muss, Hyman B.; Shea, Thomas C.
Summary: Bendamustine in combination with rituximab (BR) has been associated with high response rates and acceptable toxicity in older patients with relapsed/refractory diffuse large B‐cell lymphoma (DLBCL). Evaluation of BR is warranted in the front‐line setting for DLBCL patients not eligible for anthracyclines or for the elderly. In this phase II study, we enrolled DLBCL patients aged ≥65 years who were poor candidates for R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) to determine the efficacy and safety of BR in previously untreated stage II–IV DLBCL. Twenty‐three patients were enrolled with a median age of 80 years. 52% of patients presented with poor functional status (Eastern Cooperative Oncology Group performance score of ≥2). The overall response rate was 78% with 12 complete responses (52%). At a median follow up of 29 months, the median overall survival was 10·2 months and the median progression‐free survival was 5·4 months. The most common grade 3/4 adverse events were haematological. Combination therapy with BR demonstrates high response rates as front‐line therapy in frail older patients with DLBCL, but survival rates were low. BR should be used with caution in future clinical trials involving older DLBCL patients with poor functional status.